Kepatuhan Penderita Hipertensi terhadap Diet di Wilayah Kerja Puskesmas Guntur Kabupaten Garut - Tantri Puspita; Elang M Atoilah (Jurnal Medika Cendikia, 2018)
Hypertension is a factor of morbidity and mortality in the world. Dietary arrangement is a cause of hypertension incidence that can be changed. This is a technique of hypertension handling approach. This study aims was to analyze dietary control of people with hypertension. This study is a secondary analysis of the previous study data. Amount of 155 respondent data were analyzed in descriptive form. The results showed that more than a half of respondents were female (70.3%), mostly respondents were elderly (54.2%), and almost all respondents were graduated from primary school (79.4%). Out of four types of diet about salt, protein, fat and fiber, three diets need to be changed namely the use of salt (salt-containing foods), types and ways of processing protein sources also types and sources of fat consumed. Thus, health workers are expected to continue to provide interventions related dietary salt, fats and proteins specifically to people with hypertension.